GLUCOSE LEVEL IN PRE AND POST-BODY WORKOUT EXERCISE IN SUBJECTS OF AGE THIRD. (Fiep Bulletin - online, 2016)
The present study aims to study how the regular practice of bodybuilding can help decrease blood glucose levels in elderly individuals. Participated in this study 7 men and 4 women voluntarily. Glucose levels were collected before and after a weight training section of each participant. The data of blood glucose were pretraining 103.36 mg / dl _ + 19.57 mg / dL, and posttraining were 93.73 mg / dl + - 19.59 mg / dl, with a mean reduction 9,63mg / dl + _ 5,43mg / dl. According to the data obtained we compare the efficacy of the practice of bodybuilding exercises to improve blood glucose levels in elderly subjects.
Keywords: .